DISTRIBUSI PENDAPATAN DALAM PERSPEKTIF ISLAM: STAIN Mandailing Natal - Ali Topan Lubis (Program Studi Perbankan Syariah Jurusan Syariah, Ekonomi dan Bisnis Islam Sekolah Tinggi Agama Islam Negeri Mandailing Natal (STAIN MADINA), 2020)
Abstract This study aims to analyze the importance of income distribution in an Islamic perspective. In this study using the method of exploratory study, descriptive analysis in analyzing secondary data relating to these problems. The results show that the distribution of income in an Islamic perspective is based on ethics and fairness and fulfills systematic needs priorities including Ad-Daruriyah (Primary Needs), Al-Hajiyah (Secondary Needs) and At-Tashniyyah (tertiary needs). Keywords: distribution, income, Islamic